Learning Model “AWAS (Activity Watch And See) In Increasing Motivation To Learn Geography In Class XI IPS 1 SMA Negeri 1 Gantung - M. Aruna M. Aruna; Eviliyanto Eviliyanto (Journal of Geography Science and Education, 2022)
The main problems that will be solved through this Classroom Action Research are: Are The “AWAS (Activity Watch And See)” Learning Model Can Increase Learning Motivation Geography In Class XI 1 IPS SMA NEGERI 1 GANTUNG for the 2020/2021 academic year. The "AWAS (Activity Watch And See)" learning model was chosen with the assumption that it is very relevant to environmental subject matter, with the aim of being able to motivate students to be active, innovative, creative, effective and fun, as well as easy to manufacture and use.The goal to be achieved is to increase student learning motivation in the subject of Geography. The research subjects were students of class XI IPS 1 at SMA Negeri 1 Gantung, totaling 21 students. Research data were collected through daily observations and tests. Sources of data obtained from teachers, peers and students. The action hypothesis is UseThe "AWAS (Activity Watch And See)" Learning Model Can Increase Motivation to Learn Geography in Class XI 1 Social Studies at SMA Negeri 1 Gantung for the 2020/2021 Academic Year. The results showed that the use of the "AWAS" learning model in subjects in Geography on basic environmental competencies could increase students' learning motivation in class XI IPS 1 SMA Negeri 1 Gantung. This is evident from the learning achievement test data also shows an increase, namely in the pre-cycle as many as 11 students (47.6%) achieved the KKM with an average of 75.76, in the first cycle students who achieved completion were 61, 9% or 13 students. with an average of 76.57 and in the second cycle of 85.7% or 18 students with an average of 79.90.So after the whole cycle is done, it can be concluded that the use of The "AWAS (Activity Watch And See)" Learning Model Can Increase Learning Motivation Geography In Class XI 1 Social Sciences at SMA Negeri 1  for the 2020/2021 academic year. The obstacles faced in this AWAS learning are the lack of time allocation, the lack of mastery of using the Windows Movie Maker application (other applications). However, this obstacle can be anticipated by using a powerpoint that is already familiar to students